Pengaruh Product Knowledge, Online Customer Review (OCR) dan Perceived Enjoyment Terhadap Niat Beli Smartphone Dengan Price Discount Sebagai Variabel Moderasi (Studi Pada Konsumen Situs Jual Beli Online Shopee) - MM, YULIDA, SE, (Equator Journal of Management and Entrepreneurship (EJME), 2019)
This research aims to find out the effect of Product Knowledge, Online Customer Review and Perceived Enjoyment towards Purchase Intention with Price Discount as the Moderation Variable (A Study on The Customers of Online Market Place Shopee). This research is a survey research because the data were gathered from the questionnaire distributed to a group of people as the sample of the population. The data analysis shows that Product Knowledge, Online Customer Review and Perceived Enjoyment have affected the customer’ Purchase Intention significantly, yet Price Discount has not significantly moderated Product Knowledge with Purchase Intention.Keywords: Product Knowledge, Online Customer Review, Perceived Enjoyment, Purchase Intention and Price Discount.